Elaboración de un material audiovisual, sobre la aplicación de la musicoterapia psicoprofiláctica, para favorecer el proceso de embarazo desde el quinto mes de gestación, en mujeres adolescentes de 14 a 16 años en el sector de Chilibulo - Muñoz Vasco, Raúl Clemente (2015)
Through this work audiovisual material result of a process of preventive intervention with music therapy, psycho and prenatal stimulation, led a group of pregnant adolescents from the fifth month of pregnancy, Chilibulo Parish, located on the slopes of shows Unguí hill, south of Quito. The design and application of the product is carried out in educational institutions in the area, between August and November 2014 through 10 psychoprophylactic prenatal music therapy sessions of 2 hours, with a group of 5 teenagers and their respective partners, ages ranging from 16 to 20 years, whose pregnancy fluctuates between the fifth and seventh month of pregnancy when starting the workshops. The theoretical framework for product realization consists of 3 chapters are: adolescence as a period of transition, their realities and difficulties; pregnancy in adolescence as an analysis of the causes, how it affects your life and the ways it faces; and prenatal psychoprophylactic music therapy as a great chapter covers definitions, techniques and methodologies applied to physical and psychological preparation of the mother through the effects of music, stimulation and the link. In chapter four the design, implementation and evaluation of the product is made. Finally, conclusions and recommendations, where achievements and lessons obtained is expressed, both personally and professionally presented.